STRATEGI GURU DALAM MENGEDUKASI ORANG TUA SISWA RA INTISYARUL ULUM UNTUK MENINGKATKAN PEMAHAMAN LITERASI DIGITAL DALAM PENDAMPINGAN ANAK USIA DINI - Magnolia Nerelina Puspa; Robiatul Adawiyah (STKIP Subang, 2025)
The rapid development of digital technology presents significant challenges in early childhood education, particularly in relation to parental assistance in children’s use of digital devices at home. Parents play a crucial role in shaping children’s digital habits; however, not all parents possess adequate digital literacy skills. This study aims to describe teachers’ strategies in educating parents of RA Intisyarul Ulum students to enhance digital literacy understanding in supporting early childhood development. This research employed a qualitative descriptive approach. The research subjects included classroom teachers, the school principal, and parents of Group A students at RA Intisyarul Ulum. Data were collected through observation, interviews, and documentation. The findings indicate that parents’ digital literacy understanding varies considerably. Teachers implemented several strategies to educate parents, including parent meetings, personal communication, and the use of school communication media. The educational efforts focused on increasing parents’ awareness of the positive and negative impacts of digital device use, the importance of parental guidance, and encouraging alternative non-digital educational activities for children. These strategies contributed to positive changes in parental attitudes toward guiding children’s digital use. The study highlights the importance of collaboration between teachers, parents, and schools in strengthening family digital literacy to support healthy early childhood development in the digital era.